CORRELATION BETWEEN DURATION OF PLAYING VIDEO GAMES AND UPPER TRAPEZIUS MYOFASCIAL PAIN SYNDROME IN ADOLESCENTS - Susanto, Iwan; Thanaya, Sayu Aryantari Putri; Wahyuni, Nila; Putra, I Putu Yudi Pramana (Sport and Fitness Journal, 2022)
Some things can cause a person to have a dependence on using a computer just like office work or in terms of getting entertainment such as playing video games among adolescents. Some research leads to the duration of playing video games which is one of the risk factors of the MPS. The prevalence of MPS in general population varies by up to 85%. The method used in this study is an analytical observational method with a cross sectional approach. This study used simple random sampling techniques and the study subjects were observed with a one-time measurement of dependent variables. This research design was used to find out whether there was a relationship between the duration of playing video games and myofascial pain syndrome of upper trapezius muscle in adolescents in Denpasar City. The results showed from the total of 59 study samples, there were 46 samples (78.0%) who had upper trapezius MPS and as many as 13 samples (22.0%) who did not experience upper trapezius MPS. The distribution of research samples that experienced MPS was more in adolescents who had excessive duration of playing video games (>2 hours / day) which was 45 samples (76.3%) than samples who had MPS with a normal duration of playing video games (<2 hours / day). The conclusion of this study is that there is a significant correlation (p = 0.000) between the duration of playing video games and MPS of the upper trapezius muscle in adolescents in Denpasar City.